PLAN-M; Mycobacteriophage Endolysins Fused to Biodegradable Nanobeads Mitigate Mycobacterial Growth in Liquid and on Surfaces - Davies, Courtney G.; Reilly, Kerri; Altermann, Eric; Hendrickson, Heather L. (Frontiers in Microbiology, 2021)
The Mycobacteria are a genus of Actinobacteria that include human pathogens such as Mycobacterium tuberculosis (TB). Active TB disease can spread by airborne transmission to healthcare workers and to their community. The HHMI SEA-PHAGES program has contributed to discovering bacteriophages that are able to infect M. smegmatis MC2 155, a close relative of M. tuberculosis. This collection of diverse Mycobacteriophages is an excellent resource for trialling bacteriophage-sourced enzymes in novel applications. Herein we measured the ability Mycobacteriophage endolysins to lyse their host strain when functionally fused to biodegradable polyhydroxyalkanoate (PHA) nanobeads. PHA nanobeads facilitate both the expression and the application of enzymes to surfaces and have been demonstrated to stabilize a wide array of proteins for practical applications whilst eliminating the challenges of traditional protein purification. We selected two Lysin A and six Lysin B homologs to be functionally fused to the polyhydroxyalkanoate synthase C (PhaC). Expression of these constructs resulted in functional lysins displayed on the surface of PHA nanobeads. The lysins thus directionally displayed on nanobeads lysed up to 79% of the M. smegmatis MC2 155 population using 80 mg/mL of nanobeads in pure culture. In order to determine whether the nanobeads would be effective as a protective layer in PPE we adapted a fabric-based test and observed a maximum of 1 log loss of the cell population after 5 h of exposure on a textile (91% cell lysis). Lysin B enzymes performed better than the Lysin A enzymes as a protective barrier on textiles surface assays. These results suggest that bacterial endolysins are efficient in their action when displayed on PHA nanobeads and can cause significant population mortality in as little as 45 min. Our results provide the proof-of-principle that Mycobacteriophage endolysins can be used on functionalized nanobeads where they can protect surfaces such as personal protective equipment (PPE) that routinely come into contact with aerosolised bacteria.